Brine Effluents: Characteristics, Environmental Impacts, and Their Handling - Danu Ariono; Mubiar Purwasasmita; I Gede Wenten (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Brine discharge is one of the largest sources of wastewater from industrial processes. Because of the environmental impacts arising from improper treatment of brine discharge and more rigorous regulations of pollution control, industries have started to focus on waste minimization and improving the process of wastewater treatment. Several approaches have been proposed to provide a strategy for brine handling by recovering both brine and water or to remove pollutant components so it complies with environmental regulations when discharged. One of the most promising alternatives to brine disposal is reusing the brine, which results in reduction of pollution, minimizing waste volume and salt recovery. The brine may also contain valuable components that could be recovered for profitable use. Also, water recovery from brine effluent is generally performed to save water. In the case of rejected brine from desalination plants, water recovery from higher brine concentrations has huge potential for salt production. This paper gives an overview of different types of brine effluents, their sources and characteristics. Also discussed are impacts of brine on the environment and management options related to their characteristics.